(untitled) (Journal of Medical & Health Sciences Review, 2026)
Background: Children with Autism Spectrum Disorder (ASD) frequently present with postural and balance impairments. Physical therapy interventions focused on these balance and posture deficits are crucial for increasing functional independence and improving social participation among autistic children. Objective: The objective of this narrative review is to synthesize controlled intervention literature from the past five years, 2020–2025 (1-5) regarding balance training for autistic children and youth focusing on Center of Pressure (CoP) metrics as outcome variable. Methods: A total of 5 controlled trials, including randomized controlled trials and quasi-experimental designs, were included in this narrative review analysis. Findings: Multiple balance focused interventions including psychomotor programs, virtual reality, short session of hippotherapy and therapeutic horseback riding showed consistent improvement in CoP measures and other parameters associated with posture and balance in children and youth with autism. Conclusion: Structured, individualized balance intervention programs support autistic population in their balance improvement and rehabilitation. Despite the positive correlation seen in all these experiments, study heterogeneity and limited number of strictly experimental studies focused on CoP metrics for postural sway in autistic children in the given time period are clear limitations which must be considered for future studies.